Parameter estimation of photovoltaic models based on improvement of moutain gazelle optimizer algorithm - Salama AbdElminaam, Diaa; Saleh Alluhaidan, Ala; H. Elashmawi, Walaa; Shawky Farahat, Ibrahim; Al Tawil, Arar; Adel Nabih, Sandy; A. El-Rahman, Sahar (Frontiers in Energy Research, 2025)
IntroductionThe mountain gazelle (Gazella gazella) is a native species to the Middle East and has experienced a notable population decline due to human-induced habitat loss and fragmentation. In Saudi Arabia, the current status and distribution of this species remain poorly understood, necessitating data-driven conservation assessments.Methods, Results, and DiscussionThis study combined recent occurrence records with remote sensing and GIS-based environmental variables to model suitable habitats for the mountain gazelle using the MaxEnt algorithm. Key predictors included vegetation indices, land cover types, and elevation. The results identified core habitat areas in the western and southwestern regions, some of which fall outside current protected zones. These findings underscore the importance of expanding conservation areas and demonstrate how spatial modeling supports effective wildlife management in arid environments.